DIVERSITY OF LIFE VALUES OF POLES – SPATIAL AND DYNAMIC RECOGNITION - Szubert, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The study concerned the diversity of life values espoused by contemporary Poles. The analysis was performed in spatial terms (division of the country into districts) and in time (years 2000-2013). The main purpose of the study was to verify the two hypotheses: that there exists diversity of respected values in terms of space and time, and that in this diversity there are some regularities. To accomplish this purpose the classical techniques of spatial data analysis (Moran’s I global and local statistics and spatial regimes) and the method of cluster analysis were used. The sources of data were the results of the largest panel research in Poland called “Social Diagnosis”.During the analysis, it was found that life values are varied in terms of time and space, for Poles the most important value is health, in the last years non-material values (marriage, children, God) become more important and material values (money, work) depreciates, Masuria region is the most characteristic one in terms of different life values then in the rest of districts (values related with personal development are more significant in this region), it may be also noted a difference between west and east of the country (west is more materialistic, east more familiar and spiritual) and the spatial autocorrelation is not high and significant in only some cases (some years, some types of values).